Diagnóstico laboratorial para o vírus dengue em líquido cefalorraquidiano : a detecção do antígeno NS1 como uma nova ferramenta - Araújo, Fernanda Montenegro de Carvalho (2011)
The first cases of dengue fever in Ceará State occurred in August 1986. The disease has become endemic with a gradual increase in severe cases, some showing atypical manifestations, with involvement of the central nervous system (CNS). In order to study specific laboratory diagnosis of dengue in cerebral spinal fluid (CSF) samples aiming to implement the findings related to cases of neurological manifestations in the years of 2005, 2006, 2007 and 2008, 346 CSF samples collected from 346 patients were studied: the first group comprised 163 patients with fatal outcomes who were autopsied in Death Verification Service (DVS); the second group comprised 183 patients who attended at São José Hospital (SJH). Diagnostic methods used for CSF analysis were virus isolation in cell culture, RT- PCR, ELISA for IgM Ab and NS1 Ag detection and immunochromatography for IgG detection. A commercial kit for detection of NS1 Ag in serum was evaluated for use in CSF for the first time, and presented a sensitivity of 50% (CI 9.29-70.1) and a specificity of 100% (CI 94-100). In the first group with 163 individuals, 90 patients had infection with DENV, and from these, 46 (51.1%) were positive for dengue in CSF: one isolation of DENV-3, seven detections by RT-PCR ( four of DENV-3 and three of DENV-2), 26 NS1 Ag and 27 IgM Ab by ELISA; 38 were positive for IgG by immunochromatography. CSF added 27.8% (25/90) positive cases in the diagnosis of dengue negative in other biological samples. The clinical manifestations observed in 46 cases of deaths positive for DENV in CSF were: hyperthermia 65%, headache 50%, vomiting 30.4%, disorientation 30.4%, dyspnea 28%, polymialgia 28%, asthenia 28%, agitation 26%, abdominal pain 17%, diarrhea 16%, fall sensory 10.8% and cough 10.8%. Considering the clinical and laboratory data characterizing a CNS involvement in patients with positive CSF samples for DENV were found the following neurological disorders: 19 (41.3%) encephalitis, 14 (30.4%) meningoencephalitis and 13 (28.3%) meningitis. In the second group, all 183 CSF samples were negative for bacteria and fungi. Five cases were positive (2.7%), two for NS1 Ag and three for IgM Ab. Of the positives, four patients were hospitalized and one patient was treated at the clinic. Four patients were healed and one died. The clinical associated with suspected cases of meningitis was fever, headache, vomiting and neck stiffness. The positivity for DENV in CSF was higher in cases coming from the DVS (28.2), than the cases from SJH (2.7%), p< 0.000 (CI 4. 21-25.37) and Relative Risk of 10.33 times. The results from the study showed that there was CNS involvement in dengue cases in both groups, with a greater involvement in the cases referred from DVS. Given what has been found, it would be convenient to suggest that, in an endemic area of dengue, patients with neurological symptoms consistent with encephalitis and meningitis, showing or not classic sings of dengue fever, should be investigated for these viruses. However, prospective studies of cases with neurological manifestations of dengue are still needed to know and better understand the involvement of the CNS infection by DENV.